Inhalation Apparatus for Generating Sarin and Soman Toxic Vapors - Lucie Ševelová; Josef Vachek; Jiří Bajgar (Acta Medica, 2003)
The developed inhalation system is a dynamic and whole-body exposure model designated for generating sarin or soman vapors. It consists of an evaporating apparatus, an inhalation chamber and a carbon filter. The inhalation chamber is made of stainless steel and its total volume is 36 l. The concentration of organophosphorus compound depends on airflow through the chamber, syringe volume of the dosing pump and dosing speed. For determination of organophosphorus compound (OPC) concentration, a modification of Ellman method is used. At generating of vapors in the inhalation chamber the means of the yield were 61.4 ± 6.6 % for sarin and 35.8 ± 3.5 % for soman. The better yield for sarin than for soman, because of the higher volatility of sarin in comparison with soman was achieved. The stable concentration of the OPC for several hours could be maintained in the inhalation chamber when only relatively small amount of the OPC is used. Using the developed inhalation system LCt50 for sarin and for soman in rats was determined. At 1 h exposure the LCt50 values were 4.72 mg.h-1.m-3 for sarin and 4.81 mg.h-1.m-3 for soman. The results presented show that the inhalation chamber successfully fulfils the role of instrument for inhalation intoxication of small laboratory animals with highly toxic OPC.